The Appalachian Regional Commission Education Advisory Committee. Interim Report - Alden, Vernon; Appalachian Regional Commission, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1968)
The primary purpose of the Education Advisory Committee is to indicate priorities for the allocation of resources by the Appalachian Regional Commission and states of the region. Planning and study by the Committee has been directed to 4 general areas: pre-school education, elementary and secondary education, higher education, and occupational preparation. Following a discussion of each of the first 3 areas, the major portion of the report is concerned with manpower needs of the region and current programs for occupational preparation since it was felt by the Committee that improvement in this area would have the greatest economic and overall effect on the region. Appendix titles are: A Suggested Way To Relate Employment Trends and Vocational Education Planning; Historical Problems, Definitions, and Critiques of Current National Programs; and Formation and Operations of State Education Committees. (DK)
Educational level discussed: Early Childhood Education.
Educational level discussed: Elementary Education.
Educational level discussed: Higher Education.
Educational level discussed: Preschool Education.
Educational level discussed: Secondary Education.
Educational level discussed: Two Year Colleges.
Keywords: Administrative Organization; Community Planning; Early Childhood Education; Educational Quality; Elementary Education; Facilities; Higher Education; Labor Needs; Occupational Information; Preschool Education; Professional Personnel; Rural Areas; Secondary Education; Special Education; Teacher Characteristics; Technical Education; Two Year Colleges; Vocational Education; Appalachia